A plural University between experience and research: Design in San Marino - Alessandra Bosco; Michele Zannoni (Agathón)
According Gropius «Our century has produced the expert type in millions; let us make way now for the men of vision» (1955). In 1937, Walter Gropius expressed one of the tenets underlying the Design programmes at the University of San Marino. Against all specialism and avoiding the constant pursuit of an acceleration driven by technological innovation and constantly updated tools, Design in San Marino places the person and his relationships at the centre of its educational curriculum. The paper relies on examples and experiences to argue the reasons, methods and choices made by the group of teachers who designed and coordinate the course.